Some Worrisome Issues Surrounding the Ambit of the Copyright and Neighboring Rights Law of Ethiopia: A Comparative Legal Analysis - Ashagre, Aschalew (Bahir Dar University Journal of Law, 2022)
In 2004, Ethiopia proclaimed the Copyright and Neighboring Rights Protection Proclamation, which is still operational, to give adequate safeguards to copyright and neighboring rights in the country. To this end, the law made several commendable departures as compared to the provisions of the 1960 Civil Code of Ethiopia (which were meant to regulate the rights of authors of artistic and literary works). One of the conspicuous improvements the Copyright Proclamation made is determining its scope of application (defining the ambit of the law), since doing so is instrumental for the proper implementation of the law which in turn helps to furnish proper protection to the rights of authors and owners of neighboring rights recognized under the law. Nonetheless, a close examination of the of the relevant provisions of the law under consideration reveals that there are certain critical problems in relation to its scope of application which may overshadow the apt enforcement of the law. Hence, this author feels that it is time to analyze the problems and suggest relevant remedies that may be utilized by the Ethiopian legislature in the course of amending the law. This piece is aimed at making a thorough analysis of the provisions of the Copyright Law germane to the agenda under discussion, and forwarding possible recommendations to the problems so identified in the course of this research.